Coping in men operated for larynx cancer - Andrés-Villas, Montserrat; Torrico, Esperanza; Remesal, Raquel (Anales de Psicología / Annals of Psychology, 2012)
This study looks at the main coping strategies used by a sample of men who had undergone operations for larynx cancer, assessing possible differences with a sample of healthy men. We also try to gauge what the partners of these men think about this subject. We use the “Ways of Coping Scale” of Lazarus & Folkman (WCS) adapted to Spanish by Sánchez-Cánovas (1991). The coping strategies used most by the larynx cancer patients are “Distancing” and “Positive Re-assessment”. Unlike the larynx operated patients, the healthy males used to a lesser extent “Acceptance of Responsibility” and “Planning”. Finally, there are no significant differences between the perceptions of the larynx-operated patients and their partners, as is the case with the healthy males and their partners. ( il0 N-GB;mso-fareast-language:AR-SA;mso-bidi-language:AR-SA'> Of the women with EDs, 17 had purgative bulimia nervosa (BN), 17 had non-purgative BN, 42 fulfilled the majority of DSM-IV-TR criteria for BN and 22 fulfilled the majority of criteria for anorexia nervosa (AN). The Positive and Negative Emotional Experience Frequency Scale was designed ad hoc for the study. The results revealed that women who experienced positive emotions less frequently and negative emotions more frequently were those who fulfilled the majority of criteria for AN. Also, the clearest emotional differences were observed between those who fulfilled the majority of criteria for AN and those who fulfilled the majority of criteria for BN. In addition to having important clinical implications, these results also suggest the need to continue studying this question in order to confirm whether (as the results suggest) it is necessary to review the DSM-IV-TR non-specific disorder category.